Isolation, Identification, and Antimicrobial Susceptibility Profiles of Staphylococcus aureus from Clinical Mastitis in Sebeta Town Dairy Farms - Letebrhan Yimesgen W. Grima; Shubisa Abera Leliso; Abebe Olani Bulto; Debebe Ashenafi (Veterinary Medicine International)
A cross-sectional study was carried out in and around Sebeta town dairy farms, Finfinne special zone, Ethiopia, from December 2019 to May 2020 to isolate, identify, and test antimicrobial susceptibility profile of Staphylococcus aureus from clinical mastitis. A total of 116 milk samples were purposively collected from 57 lactating cows with clinical mastitis. Isolation and identification of Staphylococcus aureus were carried out by using primary and secondary biochemical tests. Besides, Biolog was used for microbial identification systems. To know if the isolates develop resistance to antibiotics, the antimicrobial susceptibility test (ATS) was performed on Mueller-Hinton agar by the disk diffusion method. From a total of 57 lactating cows and 116 teat quarters examined, 21.05% (12/57) and 15.52% (18/116) were positive for S. aureus from clinical mastitis, respectively. From a total of 116 milk samples collected, 15.52% (18/116) Staphylococcus aureus were isolated, and from 11 farms surveyed, about 72.72% (8/11) overall farm prevalence of clinical mastitis due to S. aureus was recorded. All the 18 Staphylococcus aureus isolates were found susceptible to sulphamethoxazole/trimethoprim, erythromycin, gentamicin, ciprofloxacin, and chloramphenicol. However, high level of resistance was observed to common drugs such as penicillin (88.89%, 16/18) and tetracycline (61.11%, 11/18). The observed high level of resistance to penicillin and tetracycline also indicates the need to visit our treatment guidelines for mastitis caused by Staphylococcus aureus. Therefore, improved management and early treatment of the cases with drug of choice after the antimicrobial susceptibility test for each specific case can reduce chance of further development of resistance and are imperative to tackle clinical mastitis occurring at Sebeta and other similar farms in Ethiopia.